Computational Exploration Toward Tunnel Oxide Passivated Contact (TOPCon) Solar Cells: Tailoring Higher Efficiency. Issue 4 (25th January 2022) - Zhou, Jiakai; Ren, Chengchao; Su, Xianglin; Liu, Xiaoning; Huang, Qian; Zhang, Xiaodan; Hou, Guofu; Zhao, Ying
Abstract: Despite the inescapable technical challenges and unclear operating mechanisms, the last few years have witnessed considerable advances in tunnel oxide passivated contact (TOPCon) structured solar cells, most of which are centered around improving the device performance so as to truly become a step forward from current mainstream technologies. However, a systematic numerical exploration is urgently required to gain a thorough understanding of the effect of the core parameters of the device on the final performance. Here, the numerical simulation way is used to explore the potential of TOPCon technology, focused on the pursuit of higher efficiency. An exhaustive analysis concerning tunnel SiO x and doped polysilicon (poly‐Si) with field passivation effect is carried out to tailor excellent surface passivation. The simulation also suggests that the ultra‐thin SiO x with extremely low pinhole density can suppress the recombination of carriers, thus promoting the passivation quality. Additionally, simulation research is conducted on the potential of using poly‐SiO x (n + ) as the doped layer, and an efficiency of 27.60% is realized via adjusting the optimal band gap and dopant concentration. Briefly, this work presents a comprehensive computational analysis of the tunnel oxide, doped layer and their synergistic impacts on the final performance. Abstract : Aiming to simultaneously realize a higher efficiency, different paths by AFORS‐HET are explored. The main content in this paper is to assess the impacts of critical factors on final efficiencies, including oxide thickness, doping, carrier transport, D it and D ph . Besides, a strategy for designing an optimized poly‐SiO x (n + ) doped layer is proposed, leading a better final performance.